Poster Lingkungan sebagai Media Pengembangan Literasi Persuasif dan Kreativitas Visual Siswa Kelas VI SD: Analisis Penggunaan Media Visual dalam Pembelajaran Berorientasi Lingkungan - Yuni Asih; Daroe Iswatiningsih; Lirra Zanni; Cebeng Alhudayatul Ustadza (STKIP Subang, 2025)
This study aims to describe the ability of sixth-grade students in writing persuasive texts, creating illustrations, and integrating both into environmental-themed posters. The research subjects consisted of 28 sixth-grade students divided into seven groups, each producing one poster. The study employed a qualitative descriptive approach using observation, interviews, and documentation techniques, as well as data analysis based on the Miles & Huberman model to obtain a comprehensive picture of the students’ processes and products. The findings indicate that most groups were able to write persuasive texts that were concise, clear, and engaging, with sufficient appeal to influence readers. The illustrations produced generally aligned with the persuasive messages, demonstrated visual creativity, and reinforced the meaning of the texts, although some groups lacked detail in their drawings. In terms of integration, the majority of posters were communicative and creative, as the texts and illustrations supported each other, effectively conveying environmental messages. However, certain groups still required guidance in balancing text and images to achieve more proportional and aesthetically pleasing posters. The study concludes that environmental posters are effective as a medium to enhance persuasive writing skills, foster visual creativity, and cultivate environmental awareness among elementary school students. Environmental posters prove to be a contextual, creative, and meaningful learning medium, as they integrate literacy, art, and character education. Thus, the use of posters not only develops academic skills but also instills social and environmental values essential for shaping young generations with strong character.